The Influence of Health Education and Training on Knowledge and Skills of KSR Students in Sprain and Strain First Aid using the RICE (Rest, Ice, Compression, Elevation) Method - Mawarda, Ulfa; Nurjannah, Misbah (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Sprain is an injury that occurs in the ligaments and strains are injuries to muscles and tendons. Sprains and strains occur as a result of strenuous daily activities, or during sports, if not treated seriously, appropriately and correctly can cause severe injury, disability, and can even lead to death. So the need for knowledge and skills in the Prevention of injury first aid so as to minimize the occurrence of injury. This study aims to analyze the effect of providing health education and training on the knowledge and skills of KSR students in first aid sprain (sprain & strain) with the RICE method in Samarinda. The design of this study is a quasi experiment with one group pretest-posttest approach. The sample in this study amounted to 72 respondents using simple random sampling. Data collection using questionnaires and observation sheets. The level of First Aid knowledge of sprains (strains & strains) with the RICE method before health education was obtained by 29 students 40.3% categorized as less and after an increase of 34 students 47.2% in the good category. As for the level of first aid skills sprains (strains & strains) with the RICE method before training obtained the majority of 39 students 54.2% categorized sufficient and after an increase of 42 students 58.3% categorized good. So it can be concluded that there is an influence of health education & training on the knowledge and skills of KSR students on first aid for sprains (strains & strains) with the RICE method in Samarinda.